Axiological transformation of society – signal to the formation of spiritual values of new generation - Katrenka, Aksana A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article is devoted to the problem of transformation of children's spiritual values. The results of the theoretical analysis of the problem area are given. The analysis of Belarusian and Russian research has shown that there is a risk of spiritual infantilization of the new generation. The increasing importance of material goods, the dominance of selfish desires and the contradictory of the personal of valuable constructs of children and youth causes anxiety. The results of empirical research of spiritual values of the new generation through the example of primary schoolchildren are represented. The inconsistency and underdevelopment of children's spiritual values, because of the incorrect family upbringing are revealed. Also the causes of low spirituality and the mistakes of parents' upbringing are also described. The psychological recommendations for the upbringing of values of children are provided.
Keywords: values; spiritual values; transformation of basic values; low spirituality; mistakes of parent upbringing; targeted education of spiritual values; psychological recommendations